Currículo e interdisciplinaridade profissional: base para uma nova gestão empreendedora - Soares, Odair Silva (2016)
The way how management, and more specifically entrepreneurship, is taught, learned and practiced, with theory and practice still based on a Cartesian view, has provoked uneasiness and the desire to develop this research. Our choice in the development of this issue was not to deal with the traditional studies on the syllabus, but notice how the conception of knowledge and its unfoldings may historically have affected the current view of management and entrepreneurship. Our professional career, rich in diverse experiences, allowed to perceive interdisciplinarity as a posture and a way of articulating the imbricated knowledge on the basis of entrepreneurial action and management of micro and small enterprises. The qualitative research was articulated around the axis of interdisciplinarity and entrepreneurship in a perspective to envision building an entrepreneurial ecosystem. Out of a dense literature screening, time was used as the thread line. In this perspective, analyzing the transition from the industrial society to the knowledge society, the research identified in the study of the complex thinking an approach that has the germ of interdisciplinarity. The objective of the research was to try to unveil at what extent interdisciplinarity and entrepreneurship are identified and can contribute in a decisive way and various dimensions in the micro management and small enterprises in everyday practice and theoretical production, currently so rare. Using the interdisciplinar research methodology by Fazenda and Japiassu and life story by Pineau, the researcher's memories of rich experiences were rescued in interdisciplinary articulations establishing dialetics to management and entrepreneurship theorists like Drucker, Filion and Dolabella, among others. Along the way, it was identified how the interdisciplinar vision is present in the entrepreneurial path, pointing to the urgent need for an ecosystem that contributes to the economic and social development at the regional and national level. At the end of the studies it is clear that the twenty-first century is the interdisciplinar and entrepreneurship century. You can not be an entrepreneur without being interdisciplinar. Interdisciplinarity, as an attitude, is an entrepreneurial practice, marked by courage and boldness. Both, courage and boldness are necessary for a new syllabus, not only in the epistemological area of management and entrepreneurship, but also for professionals in other fields, as all are involved in the market